Bend of the river [videorecording (DVD)] - Mann, Anthony, 1906-1967; Stewart, James, 1908-1997; Kennedy, Arthur, 1914-1990; Hudson, Rock, 1925-1985; Gulick, Bill, 1916-2013 (Universal Studios, 2008)
As a former outlaw turned wagon train guide, Stewart is pitted against warring Indians, murderous hijackers and a traitorous ally as he attempts to lead a group of settlers through the treacherous Oregon wilderness.